Neuropsychiatric Disorders in Parkinson’s Disease: What Do We Know About the Role of Dopaminergic and Non-dopaminergic Systems? - Dujardin, Kathy; Sgambato, Véronique (Frontiers in Neuroscience, 2020)
Besides the hallmark motor symptoms (rest tremor, hypokinesia, rigidity and postural instability), patients with Parkinson’s disease (PD) have non-motor symptoms, namely neuropsychiatric disorders. They are frequent and may influence the other symptoms of the disease. They have also a negative impact on the quality of life of patients and their caregivers. In this article, we will describe the clinical manifestations of the main PD-related behavioral disorders (depression, anxiety disorders, apathy, psychosis and impulse control disorders). We will also review clinical and preclinical literature regarding the underlying mechanisms with a focus on the role of the dopaminergic and non-dopaminergic systems.